Peak bone mineral accrual and age at menarche in adolescent girls: A 6-year longitudinal study - McKay, Heather A.; Bailey, Donald A.; Mirwald, Robert L.; Davison, K.Shawn; Faulkner, Robert A. (The Journal of pediatrics, 1998)
Background And Objectives: The greatest increase in bone mineral contentoccurs during adolescence. The amount of bone accrued may significantly affect bone mineral status in later life. We carried out a longitudinal investigation of the magnitude and timing of peak bone mineral content velocity (PBMCV) in relation to peak height velocity (PHV) and the age at menarche in a group of adolescent girls over a 6-year period. Methods: The 53 girls in this study are a subset of the 115 girls (initially 8 to 16 years) in a 6-year longitudinal study of bone mineral accretion. The ages at PBMCV and PHV were determined by using a cubic spline curve fitting procedure. Determinations were based on height (n = 12) and bone (n = 6) measurements over 6 years. Results: The timing of PBMCV and menarche were coincident, preceded approximately 1 year earlier by PHV. Correlation showed a negative relationship between age at menarche and both peak bone mineral accrual (r = –0.42, P < .002) and PHV (r = –0.45, P < .001). Conclusions: This longitudinal study demonstrated the close associationbetween age at PBMCV and age at menarche and confirmed the relationship between greater PBMCV and PHV in earlier, as compared with later, maturing girls. (J Pediatr 1998;133:682-7)